The Role of Iron and Copper on the Oligomerization Dynamics of DR_2577, the Main S-Layer Protein of Deinococcus radiodurans - Farci, Domenica; Guadalupi, Giulia; Bierła, Katarzyna; Lobinski, Ryszard; Piano, Dario (Frontiers in Microbiology, 2019)
Surface (S)-layers are cryptic structures that coat the external surface of the bacterial cell in many species. The paracrystalline regularity of the S-layer is due to the self-assembling of one or more protein units. The property of self-assembling seems to be mediated by specific topologies of the S-layer proteins as well as the presence of specific ions that provide support in building and stabilizing the bi-dimensional S-layer organization. In the present study we have investigated the self-assembling mechanism of the main S-layer protein of Deinococcus radiodurans (DR_2577) finding an unusual role played by Fe3+ and Cu2+ in the oligomerization of this protein. These findings may trace a structural and functional metallo-mediated convergence between the role of these metals in the assembling of the S-layer and their well-known roles in protecting against oxidative stress in D. radiodurans.